QUALITY OS LIFE IN PATIENTS WITH SPINAL CORD INJURY SUBMITTED TO PHYSIOTHERAPY NEUROFUNCTIONAL AND ACQUATIC PHYSIOTHERAPY. (Fiep Bulletin - online, 2011)
Introduction: Patients with spinal cord injury with different etiologies can have functional limitations such difficulty in performing transfers, feeding, dressing, walking, among others. These changes interfere directly in the quality of life. The neurofunctional physiotherapy and acquatic physiotherapy work in order to reduce this limitation and failures, rescuing the most quality of life of these patients. The treatment in soil and in the liquid show great acceptance rates, tha ctivities become pleasant, improving self-esteem and social interaction of patients. Act directly on the improvement of functional capacity, provide early walking, increase in range of motion, increase the muscle strength, improvement in balance and equilibrium reactions, among others. Objective: To analyze the effects presented by neurofunctional and acquatic physiotherapy in patients with spinal cord injury after the submit the treatment. Methodology: Held a study with 5 volunteers of both genders, with an average of 2 years after the injury and average of age 20 years that receiving attendance in sector of neurofunctional and acquatic physiotherapy in rehabilitation clinic FAG - Assis Gurgacz College. Results: Through this study, it was the average the patients who participated in the study, can be found the improvement of 45% in Limitation by Role-Physical, 2.8% in relation from pain, 1% in the general health, 11% in relation to Social Functioning, 5% em relation to vitality and 10.6% in Limitation by Role-Emotional. However, there was a decrease of 3.2% in relation to mental health. Conclusion: It is understood that through this study that neurofunctional physiotherapy acting in conjunction with the acquatic physiotherapy can bring benefits in relation the quality of live of patients with spinal cord injury.
Keywords: Neurofunctional and Acquatic Physioterapy; Quality of life; Spinal Cord Injury